Development of sphalerite activation regularity by copper sulphate - Chettibi, M.; Abramov, A. A. (Journal of mining science, 2016)
The adsorption regularity of copper sulphate on sphalerite surface can be defined by a thermodynamic analysis of sphalerite surface state and behavior of copper sulphate in solution was made. From the results of a complete chemical calculations of the minerals surfaces state, and experimental investigation. It is showed, that corresponding to minimum charge of the covered surface, that no matter the products of copper sulphate oxidation Сu 2 (OH) 2 CO 3 or Cu(OH) 2 the pH value is a round 10,3 and the concentration of copper ions necessary for a complete activation of sphalerite should not be upper to 10-6 mol/l. The excess of the available concentration of copper ions over the necessary in solution could not define the regularity of copper adsorption on sphalerite; it is subject to Langmuir equation and depends on the concentration of copper ions. That is why the zinc sulphides activation rate increases by increasing the dispersion degree of the copper chemical bonds, the contact time and the temperature of the pulp.